Household decision-making, women's empowerment, and increasing egg consumption in children under five in rural Burkina Faso: Observations from a cluster randomized controlled trial - Moore, Emily V.; Singh, Nitya; Serra, Renata; McKune, Sarah L. (Frontiers in Sustainable Food Systems, 2022)
Malnutrition is one of the most long-suffering problems facing women and children across the world—it is endemic to many low- and low-middle income countries and is a leading comorbidity in CU5 mortality. Malnutrition and food security are gendered issues; not only are boys and girls differently affected by these issues, but societal norms and differing roles of women and men are often drivers of these different outcomes. The United Nations seeks to address both malnutrition and gender inequality by reaching its Sustainable Development Goals by 2030. Researchers have shown that women's empowerment is inextricably linked to the nutritional outcomes of children. As one dimension of women's empowerment, intra-household decision-making is an important determinant of child health and nutrition outcomes, as it can determine how resources are allocated within the household. To better understand how gender inequalities within household decision-making may contribute to child nutrition, this study examines the association between household decision-making and the adoption of behavior change to increase chicken egg consumption among infants and young children in Burkina Faso, and explores the relationship(s) between the Un Oeuf project and women's empowerment. This study analyzes data collected during the Un Oeuf cRCT (July 2018–April 2019) and additional data that were collected in conjunction with the Un Oeuf endline household survey in April 2019. Significant relationships were found between women's household decision-making about eggs and child egg consumption at the end of the project. This was true for women who did not have decision-making power at baseline (p = 0.006, OR 3.822) as well as for women who indicted having had that power and sustaining it through endline (p = 0.013, OR 6.662). Results indicate that the Un Oeuf project significantly increased women's household decision-making (p > 0.005, OR 4.045). Finally, significant relationships were found between a woman's overall level of empowerment and household decision-making power surrounding (1) what is done with household eggs (p < 0.005, OR 2.87) and (2) how foods are portioned (p = 0.012, OR 6.712). These findings illustrate the importance and potential of women's decision-making as a point of entry to improving nutritional outcomes through changes in empowerment.